2013
DOI: 10.1038/nn.3499
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous cortical activity alternates between motifs defined by regional axonal projections

Abstract: In lightly anaesthetized or awake adult mice using millisecond timescale voltage sensitive dye imaging, we show that a palette of sensory-evoked and hemisphere-wide activity motifs are represented in spontaneous activity. These motifs can reflect multiple modes of sensory processing including vision, audition, and touch. Similar cortical networks were found with direct cortical activation using channelrhodopsin-2. Regional analysis of activity spread indicated modality specific sources such as primary sensory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

77
458
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 373 publications
(538 citation statements)
references
References 50 publications
(104 reference statements)
77
458
2
1
Order By: Relevance
“…We demonstrate the presence of spontaneous infraslow activity in anaesthetized mouse cortex and that this activity exhibits regionally selective patterns, correlates with independent measures of electroencephalography (EEG) and local field potential (LFP), and is bilaterally synchronous. Importantly, intrahemispheric, spontaneous infraslow activity exhibits a patterned regional structure that is analogous to cortical motifs within higher-frequency (0.5-6 Hz) activity that we have previously described 27 . This builds upon pioneering studies in cat visual cortex which illustrated that cortical orientation representations are dynamically represented in ongoing spontaneous activity, and further, that these events may serve a preparatory role in setting default cortical sensory input parameters 30,31 .…”
supporting
confidence: 66%
See 4 more Smart Citations
“…We demonstrate the presence of spontaneous infraslow activity in anaesthetized mouse cortex and that this activity exhibits regionally selective patterns, correlates with independent measures of electroencephalography (EEG) and local field potential (LFP), and is bilaterally synchronous. Importantly, intrahemispheric, spontaneous infraslow activity exhibits a patterned regional structure that is analogous to cortical motifs within higher-frequency (0.5-6 Hz) activity that we have previously described 27 . This builds upon pioneering studies in cat visual cortex which illustrated that cortical orientation representations are dynamically represented in ongoing spontaneous activity, and further, that these events may serve a preparatory role in setting default cortical sensory input parameters 30,31 .…”
supporting
confidence: 66%
“…Furthermore, descriptions of resting-state infraslow activity in humans, non-human primates and rodents have demonstrated these networks to be robust and persistent in task-negative awake states in addition to states of natural sleep and anaesthesia 5,9,32 . Furthermore, our previous data indicated that connectivity maps from quiet awake and anaesthetized states are similar 27,33 . We observed spontaneous infraslow (o0.1 Hz) fluctuations in baseline DC-EEG and LFP recordings (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations